The neolithic revolution and contemporary variations in life expectancy - Oded Galor; Omer Moav (Brown University, Department of Economics, 2007)
This research advances an evolutionary theory and provides empirical evidence that shed new light on the origins of contemporary differences in life expectancy across countries. The theory suggests that social, economic and environmental changes that were associated with the Neolithic Revolution affected the nature of the environmental hazards confronted by the human population, triggering an evolutionary process that had a significant impact on human longevity. The empirical analysis shows that a significant portion of contemporary variations in life expectancy across countries can be traced to the differences in the time passed since the ancestors of the population of each country experienced the Neolithic Revolution.
Keywords: I12; J13; N3; O10; 330; Life Expectancy; Growth; Technological Progress; Evolution; Natural Selection; Malthusian Stagnation; Bevölkerungstheorie; Sterblichkeit; Biologie; Vorgeschichte; Technischer Fortschritt; Wachstumstheorie